CHALLENGES AND EFFORTS IN DEVELOPING A GENEROUS ATTITUDE THROUGH SHARIA FINANCE LEARNING AT KILAUAN IMPIAN KINDERGARTEN, MALAYSIA - Mia Audina; Rahmayati Rahmayati (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2026)
This study explores the challenges and efforts in developing a generous attitude in early childhood through Islamic financial education at Tadika Kilauan Impian, Malaysia. The method applied is a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results of this study show that Islamic financial education for children faces several obstacles, such as difficulties in understanding abstract concepts, lack of integration into the curriculum, limited teacher competence, and suboptimal application of values between educational institutions and families. This study reveals that approaches such as habituation of values, social activities, role modeling, and collaboration between schools and families are crucial in shaping a contextual generous attitude. Theoretically, these results indicate that Islamic financial education plays an important role in instilling values, not just in educating knowledge. In the policy context, this study recommends that a curriculum based on Islamic finance become a priority, teachers' capabilities be improved, and support from institutions be provided to uphold character education of generosity from an early age.